A150 IBD PATIENTS TRANSITIONING FROM PEDIATRIC TO ADULT CARE LACK THE NECESSARY TRANSITION SKILLS. (1st March 2018) - Cookson, T A; Klostermann, N R; Wine, E; Kroeker, K I
Abstract: Background: With the rise of inflammatory bowel disease (IBD) in pediatric patients, transition is a process that occurs more every day. In a prior study, we identified that an interactive IBD transition website was needed to assist pediatric patients with IBD make the transition from pediatric to adult gastroenterology care. This interactive website can be used to assess the transition skills of patients around the time of transfer of care. Aims: To assess the transition skills of young adults with IBD around the time of transfer of care, before and after using the newly developed IBD Transition Website. Methods: Participants between the ages of 16–18 years were recruited in the pediatric and adult IBD clinics at the Stollery and University of Alberta Hospitals. Written consent was obtained and participants were directed to the transition.ibdclinic.ca website and instructed to complete a short website assessment. After the participants complete the assessment, they are prompted to re-take the assessment after 30 days to assess if there is any change in these transition skills. Transition skills assessed include: 1) knowledge (IBD-Kid), 2) medication adherence, and 3) transition readiness (TRAQ). Results: To date, 21 patients recruited and 8 have completed the initial assessment. Demographic data of those completing the initial assessment: 75% female; 75% have Crohn's Disease; median age of 17.5. Results of the baseline transition skills assessments are shown in Table 1; scores are compared to results to literature values. 30-day post-website access scores are not yet available. Conclusions: In IBD patients transitioning from pediatric to adult care in Edmonton appear to have good knowledge and medication adherence, however show significant deficits in transition readiness skills. It is not yet known, if an IBD website intervention is able to improve these deficits. Funding Agencies: CEGIIR